Pendampingan pembuatan alat musik Klentang - Hary Murcahyanto (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2023)
Traditional music is an ancestral form of art in a society that relies on local traditions, language, and culture. One of the preserved traditional music in East Lombok is Klentang, a traditional musical instrument shaped like metal bars played in a musical ensemble. Despite its rapid development, the existence of Klentang remains safeguarded by the East Lombok community. Therefore, this research aims to accompany the production of Klentang musical instruments at Sanggar Patuh Gending to preserve the culture and advance traditional music. The study is conducted using ethnographic methods involving 18 craftsmen and 8 students. The Klentang-making process includes crafting the metal bars and their supports. The metal bars are made by heating and forging steel, followed by tuning the pitches by striking the bars with a hammer. The supports consist of bends and frames made from bamboo and wooden boards. The size and tuning of Klentang are adjusted to the diatonic tuning system intervals to produce harmonic sounds. Crafting Klentang requires skill and precision to create high-quality musical instruments. By executing this process effectively, Klentang can produce beautiful and harmonious sounds when played, ensuring the continuity and preservation of traditional Klentang music.